Analisis Strategi Bisnis Pada Toko Generation IT Service Kecamatan Mustika Jaya - Tjitrayudha, Marcel; Pardistya, Irvan Yoga (Peneliti.net, 2025)
This research analyzes the Generation IT Service business strategy using a qualitative approach with the SWOT analysis method. Data was obtained through in-depth interviews with company founders. The goal is to provide insight into the advantages, disadvantages, opportunities and threats affecting these businesses, as well as help increase competitiveness and maximize opportunities in the information technology market. Qualitative methods are used with data collection techniques such as in-depth interviews, observation, and literature study. Research variables are in the form of categories, and data analysis is carried out using an interactive data analysis model. Based on the analysis results, strategies are recommended, including store expansion, service diversification, strengthening customer relationships, and online optimization. With proper implementation, Toko Generation IT Service can strengthen its market position and overcome challenges, especially in the context of online competition.